2012
DOI: 10.1136/archdischild-2012-302143
|View full text |Cite
|
Sign up to set email alerts
|

Perthes’ disease of the hip: socioeconomic inequalities and the urban environment

Abstract: The occurrence of Perthes' disease within urban environments is high, yet this appears to be a reflection of higher socioeconomic deprivation exposure. Disease rates appear equivalent in similarly deprived urban and non-urban areas, suggesting that the determinant is not a consequence of the urban environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 15 publications
0
22
0
1
Order By: Relevance
“…ADHD and LCPD share common risk factors through inheritance or exposure, such as deprivation (Lingineni et al 2012, Perry et al 2012b), higher injury risk (Maxson et al 2009, Hailer et al 2012), and maternal and passive smoking (Garcia Mata et al 2000, Button et al 2005). Especially in adults, neurobehavioral aspects of ADHD can change from hyperactivity to more inattentiveness or depression (Yang et al 2013), which may explain the higher risk of depression in individuals with LCPD than in their controls, and which also supports our hypothesis (2).…”
Section: Discussionmentioning
confidence: 99%
“…ADHD and LCPD share common risk factors through inheritance or exposure, such as deprivation (Lingineni et al 2012, Perry et al 2012b), higher injury risk (Maxson et al 2009, Hailer et al 2012), and maternal and passive smoking (Garcia Mata et al 2000, Button et al 2005). Especially in adults, neurobehavioral aspects of ADHD can change from hyperactivity to more inattentiveness or depression (Yang et al 2013), which may explain the higher risk of depression in individuals with LCPD than in their controls, and which also supports our hypothesis (2).…”
Section: Discussionmentioning
confidence: 99%
“…Data concerning Perthes disease discharges in Scotland 21 and unpublished data from the Perthes disease register from Northern Ireland (presented at the British Orthopaedic Association congress in 2012) have similarly confirmed a decline in Perthes disease incidence, adding support to the validity and generalisability of these findings.…”
Section: The Urban Environmentmentioning
confidence: 78%
“…Perthes disease discharge data from Scotland were used in 2012 to investigate this relationship. 21 Scotland is a particularly good setting for this investigation as it is largely rural despite having a number of major cities and some of the UK's most deprived areas. This study observed more Perthes disease in urban environments.…”
Section: The Urban Environmentmentioning
confidence: 99%
“…In the UK, a decline in incidence of the disease has been described, particularly in more deprived areas (Perry et al. 2012b). …”
mentioning
confidence: 99%
“…In a more recent study using data from the Scottish Morbidity Record for the period 2000–2010, the occurrence of Perthes’ disease after stratification for socioeconomic deprivation showed similar rates in urban and rural areas of Scotland (Perry et al. 2012b). …”
mentioning
confidence: 99%